5,7-Diiodoquinolin-8-yl (E)-3-(3,4-dihydroxyphenyl)acrylate - Marcin Cybulski; Michał Zieliński; Marek Kubiszewski; Olga Michalak (Molbank, 2025)
We report the synthesis of 5,7-diiodoquinolin-8-yl ester of caffeic acid and its O,O-diallyl-protected analogue. The compounds from the hybrid class were fully characterised using NMR spectroscopy and high-resolution mass spectrometry.